Analytic solution of the differential Maxwell system and its numerical implementation - Vorobiyenko, Peter Petrovich; Dmitrieva, Irina Yuriyevna (НТУ "ХПІ", 2019)
The differential Maxwell equations are solved constructively under the specific requirements in the spatial Cartesian coordinate system. The expressions of the unknown electromagnetic field vector intensities are found explicitly as the solutions of the general wave equation regarding all scalar components of the initially unknown vector field functions. The aforesaid equation is equivalent to the original Maxwell system. The present results are obtained using two new efficient operator analytical methods which application is shown also for the heterogeneous media. The numerical implementation for the particular case of the considered electrodynamic mathematical model is proposed here as well.

Запропоновано конструктивне розв'язання диференціальних рівнянь Максвелла за певних умов у просторовій декартовій системі координат. Явні вирази шуканих вектор-функцій напруженості електромагнітного поля знайдено як розв'язки загального хвильового рівняння, еквівалентного вихідній максвелловській системі. Дані результати отримано завдяки двох нових ефективних операторних аналітичних методів, застосовування яких продемонстровано також для неоднорідних середовищ. Частковий випадок розглянутої математичної моделі електродинаміки реалізовано чисельно.
Аналітичне розв'язання диференціальної системи Максвелла та його числова реалізація
Keywords: general wave equation; analytic operator methods; constructive solution; mathematical model; загальне хвильове рівняння; аналітичні операторні методи; конструктивне розв'язання